Collision tumor of endometrial hepatoid adenocarcinoma and endometrial stromal sarcoma: a rare case and literature review - Zhang, Jie; Wang, Dengfeng; Shi, Min; Zhou, Ting; Shi, Xunwei; Peng, Liping; Liu, Yang; Zhang, Guonan (Frontiers in Oncology, 2026)
BackgroundEndometrial hepatoid adenocarcinoma (HAC) is an exceedingly rare tumor. Histologically, the tumor is predominantly characterized by HAC with additional components, as documented in previous reports. The coexistence of endometrial HAC and endometrial stromal sarcoma in collision tumors is exceptionally uncommon. To our knowledge, this case represents only the second documented instance of such a collision tumor.Case presentationA 69-year-old postmenopausal woman presented with abnormal uterine bleeding, and her serum alpha‐fetoprotein (AFP) concentration was 8926 ng/mL. The initial biopsy revealed poorly differentiated adenocarcinoma. Subsequent postoperative histopathological evaluation confirmed the coexistence of endometrial HAC and endometrial stromal sarcoma. Notably, according to imaging, gross examination, and microscopy, the two tumor components were separated by distinct contact areas without evidence of migration or intermingling. The patient developed pulmonary metastases within 40 days of surgery and eventually died of the disease.ConclusionEndometrial hepatoid adenocarcinoma is an exceptionally rare tumor that frequently coexists with other pathological components. Preoperative diagnosis remains challenging, and definitive characterization relies predominantly on postoperative evaluation, particularly immunohistochemical analysis. These tumors exhibit marked heterogeneity and aggressiveness, with a propensity for lung metastasis and an overall poor prognosis. Due to the limited number of reported cases, there is no established consensus regarding the optimal treatment. Some case reports suggest that the development of hepatoid adenocarcinoma of the uterus may have some correlation with endometriosis. 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) enables the comprehensive pretreatment assessment of disease extent and the early detection of metastases. Surgical intervention remains the mainstay of treatment, but accurate evaluation of pathological characteristics is critical for selecting the optimal chemotherapy regimen. In this context, the CAP regimen—comprising cyclophosphamide, adriamycin, and cisplatin—has demonstrated superior overall efficacy. Moreover, these tumors seem to be relatively resistant to radiation therapy.